Implementation of the Resilience of God's Servants Based on the Book of 2 Timothy Among the Students of Theological College in Pontianak City, West Kalimantan - Mahengkeng, Youti; Suparti, Hana; Iskandar, Srini M; Lumintang, Danik (Technium Social Sciences Journal, 2025)
This study aims to find out the level of implementation of the resilience of God's servants, the most dominant dimensions and backgrounds that influence the level of implementation of the resilience of God's servants based on the book of 2 Timothy, in order to realize resilient servants of God among students of Theological Colleges throughout Pontianak City, West Kalimantan. From the results of the pre-survey, it was found that there were still students who did not have resilience. This study uses a quantitative method, by measuring the Four Dimensions (D) on the concept of implementing the resilience of God's servants based on the book of 2 Timothy. The results of the study show that first, the level of implementation of the resilience of God's servants is in the moderate category. Second, the most dominant dimension is Having the Ability to Survive (D2). The third most dominant background category is Length of Study (L10). Based on these data, the level of implementation of the resilience of God's servants among students of Theological Colleges throughout Pontianak City, West Kalimantan, needs to be increased from a moderate level to a high level, and produce resilient servants of God.